Assessment of depression, PTSD, and insomnia symptoms in a cohort of Palestinian migrants residing in Jordanian camps during the outbreak of the War on Gaza: occurrence and correlates - Omar Gammoh; Saleh Bazi; Ruba Al Akash; Bilal Sayaheen; Mervat Alsous; Albara Alomari (Discover Mental Health)
Abstract The present study sought to examine the occurrence and correlates of depression, PTSD, and insomnia in a cohort of Palestinian refugees residing in camps located in Jordan during the outbreak of the War on Gaza on Oct.7th.This is a cross-sectional cohort study that employed the convenient sampling method to recruit Palestinian refugees residing in Irbid and Azmi Almufti camps for Palestinian refugees. Depressive symptoms were assessed using the Patient Health Questionnaire (PHQ-9) scale. The self-reported PTSD symptoms were evaluated using the brief PTSD scale, and insomnia severity was assessed using the Insomnia Severity Index -Arabic scale (ISI-A). The data analysis from 258 participants showed that severe depression was reported in 178 participants (69%). Additionally, 127 participants (49.2%) reported severe PTSD symptoms, and 156 participants (60.5%) reported severe insomnia symptoms. Regression analysis revealed that “Residents of Azmi Almufti camp” was a significant correlate for severe depression (OR = 2.22, 95% 1.28–3.85, p = 0.004) and severe PTSD (OR = 1.81, 95% CI = 1.10–2.99, p = 0.02). The use of over-the-counter antihistamines as a sleep aid was a significant correlate severe insomnia (OR = 3.19, 95%CI = 1.17–8.71, p = 0.02) and PTSD (OR = 3.32, 95% CI = 1.34–8.21, p = 0.01). The conflict in Gaza has been observed to correlate with mental health challenges, particularly among Palestinian refugees residing in Jordan.